Resposta magnética de supercondutores estruturados: dependência com a granulometria - Trípodi, Alonso Campoi (2010)
The maximum critical current that a granular superconductor is able to transport is, in general, limited by the critical current of the weak-links (WLs), which connect neighbor grains. For samples whose intergranular critical current distributions are sufficiently narrow, the temperature dependence of the AC-susceptibility, ( ) '( ) ''( ) ACχ T=χT+iχ T, exhibits a characteristic structure, with two plateaus peaks in χ´ and two peaks in χ´´. The occurrence of an intergranular peak evidences a good control of the WL distribution concerning current transport capability, which, in general, depends on parameters that can be controlled during production of the granular samples. In order to study magnetic flux trapping in superconducting samples, one has to understand the weak-link behavior. The screening and trapping capabilities of a superconducting sample are reflected by the hysteresis loops which, properly treated, reveal the sample maximum capability to transport currents. In this work we have used niobium powder to study the magnetic response of the intergranular regions of compressed pellets; we have managed to understand the role of each of three parameters employed while preparing the pellets: pressure, grain size and its dispersion. We have studied the magnetic response (magnetization and AC susceptibility) dependence on such , controllable parameters. Dissertação de Mestrado Alonso Campoi Trípodi We noticed that samples prepared with higher pressures have larger capability to trap magnetic flux in the intergranular region and stronger WLs. On the other hand, samples with larger particles have WLs with higher critical temperatures, that is, pellets fabricated from larger particles exhibit more robust superconductivity. We have observed the Paramagnetic Meissner Effect, in the form of reentrant curves of Magnetization as a function of Temperature. Comparing pellets with different grain sizes, flux trapping was most efficient for samples with large particles and lower size dispersion. We verified also the metastable character of states prepared in such a way that flux was retained, comparing magnetization measurements before and after application of an AC field, which causes partial release of magnetic flux from intergranular regions, an effect similar to the so-called Vortex Shaking. We also conducted experiments as a function of the applied magnetic field the hysteresis loops aiming at obtaining the magnetic field dependence of the critical current, employing a critical state model for this task. We verified that, for lower temperatures, the critical current density is higher for pellets with larger particles and narrow size dispersion. In summing up, our results clearly indicate that, for a certain granulometry, larger compacting pressures lead to more diamagnetic responses, as well as to WLs with narrower superconducting transitions which turn off at larger temperatures. On the other hand, for a certain compacting pressure in pellets with narrow size dispersions, larger particles lead to stronger WLs.